2023
DOI: 10.3389/fneur.2023.1149268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strength training in fibromyalgia on balance, neuromuscular performance, and symptomatic analysis: a 12-week study protocol

Abstract: Fibromyalgia affects skeletal muscles presenting with muscle stiffness, pain, and fatigue. The exercise practice is wellstabilized and suggested for the reduction of symptoms. However, there are some gaps in the literature related to balance and neuromuscular performance in a strength training protocol. The aim of this study is to structure a protocol to verify the effects of strength training applied over a short period, on balance, neuromuscular performance, and fibromyalgia symptoms. Additionally, we intend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…There is a large body of scientific evidence to suggest that exercise and physical activity are key to improving symptoms in people diagnosed with FM [6,10,13,28], many of which include reduction in pain, improvement in perceived levels of anxiety and depression, as well as general quality of life [9,22,29]. However, FM women have relatively poor exercise adherence rates and maintain more sedentary lifestyles compared to healthy women [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of scientific evidence to suggest that exercise and physical activity are key to improving symptoms in people diagnosed with FM [6,10,13,28], many of which include reduction in pain, improvement in perceived levels of anxiety and depression, as well as general quality of life [9,22,29]. However, FM women have relatively poor exercise adherence rates and maintain more sedentary lifestyles compared to healthy women [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the great diversity of symptoms in people diagnosed with fibromyalgia, there is no consensus on what, how, and when physical activity should be performed [10]. Although aquatic exercise has classically been considered the most appropriate for reducing inflammation and improving symptoms and quality of life [6,7], other current studies have shown that strength training is one of the most effective methods for improving these health patients [11][12][13] without focusing too much on daily cardiovascular health. In addition, sedentary lifestyles predominate in this type of patient to avoid worsening of symptoms and increased pain [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Low-impact aerobic exercises, such as walking, swimming, and cycling, are effective in managing fibromyalgia symptoms [ 51 ]. Strength training and stretching exercises can also be beneficial in improving muscle strength and flexibility [ 52 ].…”
Section: Reviewmentioning
confidence: 99%